Initial Experience of Retroperitoneoscopic Surgery in Benign Renal Diseases - kunwar, Ashok kumar; Upadhyay, Amit Mani; Shrestha, Sanjesh Bhakta; Koirala, Udaya; Tiwari, Kabir; Dangal, Ganesh (Journal of Nepal Health Research Council, 2019)
Background: To review our early experience to determine the feasibility, efficacy and clinical outcomes of retroperitoneoscopic surgery in benign renal diseases.Methods: This is a prospective observational study carried out between December 2014 to March 2018. Among 14 patients enrolled in the study, 9 cases of nonfunctioning kidney underwent retroperitoneoscopic simple nephrectony, 4 cases of benign renal cortical cysts underwent decortication of cysts and one case of pelviureteric junction obstruction underwent Anderson Hynes pyeloplasty. Results: Retroperitoneoscopic nephrectomy, renal cyst decortication and A-H pyeloplasty were performed in 13 patients successfully. The procedure in one patient of RP nephrectomy converted to open surgery due to dense perinephric and hilar adhesions. Which resulted to failure to progress. The mean operative time of RP nephrectomy, decortications and pyeloplasty were 206.4 (150-248), 67.5 (60-80) and 275 minutes, average blood loss was 96.7 (50-120), 27.5 (20-30) and 70 ml, and the mean hospital stay were 3.5 (3-4), 2 (2-2) and 4 days respectively. The perioperative period was uneventful.Conclusions: Retroperitoneoscopic surgery is feasible and safe in benign renal diseases. Because of reduced post operative pain and less chances of bowel injury, retroperitoneoscopic surgery is gaining more popularity.Keywords: Nonfunctioning kidney; pyeloplasty; renal cyst; retroperitoneoscopic surgery.